17. THE DEVELOPMENT OF THE COUNTRY IS THE PLACE OF SPIRITUALITY AND ENLIGHTENMENT - Salimov Bakhriddin Lutfullaevich. Akramov Nurislombek Ilhomjonovich. (Innovative technologies in construction Scientific Journal, 2023)
In the article, it is analyzed that humanity always lives in pursuit of spirituality, that creativity and creativity are a great quality characteristic of a person, but that although a lot of work has been done and is being done in the field of spirituality in recent years, they cannot produce enough results, and the reason for this is related to the fields of spirituality and enlightenment.